2018
DOI: 10.1051/0004-6361/201833929
|View full text |Cite
|
Sign up to set email alerts
|

The possible common origin of M 16 and M 17

Abstract: Context. It has been suggested that the well-studied giant HII regions M16 and M17 may have had a common origin, being an example of large-scale triggered star formation. While some features of the distribution of the interstellar medium in the region support this interpretation, no definitive detection of an earlier population of massive stars responsible for the triggering has been made thus far. Aims. We have carried out observations looking for red supergiants in the area covered by a giant shell seen in H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…the region, which we can reconstruct thanks to their relationship with their ages. We use the cumulative mass distribution of the 24 red supergiants that we identify in the Cygnus region, following a treatment similar to that presented by Comerón et al (2016) and Comerón & Torra (2018). The number N(M) of red supergiants observed at the present time t = 0 with a mass above a certain value M can be written as…”
Section: The Star Formation History In the Cygnus Regionmentioning
confidence: 99%
“…the region, which we can reconstruct thanks to their relationship with their ages. We use the cumulative mass distribution of the 24 red supergiants that we identify in the Cygnus region, following a treatment similar to that presented by Comerón et al (2016) and Comerón & Torra (2018). The number N(M) of red supergiants observed at the present time t = 0 with a mass above a certain value M can be written as…”
Section: The Star Formation History In the Cygnus Regionmentioning
confidence: 99%
“…Globule g4 coincides with the H II region DR18, which hosts a strong IR-source (IRAS 20343+4129, MSX6G080.3624+00.4213) at near-, mid-, and far-IR wavelengths. Comerón & Torra (1999) observed DR18 at IR and optical wavelengths and found an arc-shaped nebula, externally illuminated by a nearby B0.5V star. The globular shape is most likely caused by the object's proximity to the Cyg OB2 cluster (see Fig.…”
Section: Description Of Mapsmentioning
confidence: 99%
“…(2) Friel (1995) suggested that impact of high velocity clouds on to the Galactic disk could lead to star formation in the Disk gas, a mechanism studied by Comeron & Torra (1992), who related an oblique collision of this kind to the formation of Gould's belt. The cluster formed in the process could retain some kinetic memory of the event, leading to a high z and possibly eccentric Galactic orbits.…”
Section: A2 "Unusual" Formation Scenariosmentioning
confidence: 99%